Sie sind auf Seite 1von 99

1B

1A

Answers

Answers

Chapter 1 Exercise 1A 1 {8, 11} a b {8, 11} c {1, 3, 8,
Chapter 1
Exercise
1A
1 {8, 11}
a
b {8, 11}
c
{1, 3, 8, 11, 18, 22, 23, 24, 25, 30}

d

e

{3, 8, 11, 18, 22, 23, 24, 25, 30, 32}

{3, 8, 11, 18, 22, 23, 24, 25, 30, 32}

f {1, 8, 11, 25, 30} 2 a {3, 18, 22, 23, 24} b {25,
f
{1, 8, 11, 25, 30}
2 a
{3, 18, 22, 23, 24}
b {25, 30, 32}
c
{3, 18, 22, 23, 24}
d {1, 25, 30}
3 a
− 4 − 3 − 2 − 1012345
b
24} d {1, 25, 30} 3 a − 4 − 3 − 2 − 1012345 b

4 3 2 1012345

c

− 2 − 1012345 b − 4 − 3 − 2 − 1012345 c − 4

4 3 2 10123 45

d

e

f

− 4 − 3 − 2 − 1012345
− 4 − 3 − 2 − 1012345
− 4 − 3 − 2 − 1012345
− 4 − 3 − 2 − 1012345

4 3 2 1012345

4 {7, 9}

a

b {7, 9}

 

c

{2, 3, 5, 7, 9, 11, 15, 19, 23}

d

{2, 3, 5, 11}

e

{2}

f

{2, 7, 9}

g

{2, 3, 5, 7}

h

{7}

i

{7, 9, 15, 19, 23}

j

(3, )

5 a

{a,e}

b {a,b,c,d,e,i,o,u}

c

{b,c,d}

d {i,o,u}

6 b

a

{6}

{2, 4, 8, 10}

c

{1, 3, 5, 7, 9}

d

{1, 2, 3, 4, 5, 7, 8, 9, 10}

 

e

{1, 2, 3, 4, 5, 7, 8, 9, 10}

f {5, 7}

g

{5, 7}

h {6}

7 a [−3, 1) b (−4, 5] c (− √ 2, 0) d − 1
7
a
[−3, 1)
b
(−4, 5]
c
(− √ 2, 0)
d
− 1 2 , √ 3
e
(−∞, −3)
f
(0, ∞)
g
(−∞, 0)
h
[−2, ∞)
8
a
(−2, 3)
b [−4, 1)
c [−1, 5]
d (−3, 2]
9
a
− 3 − 2 − 1 012
b
− 4 −3 − 2 − 1 0123
c
0123
d
−4 − 3 − 2 − 1 01
e
4 − 3 − 2 −1 0
f
− 2 − 1 012345
10 a
− 3 − 2 −1 0123456
b
3 − 2 − 1 0123456
c
−2 − 1 0123456
d
− 8
−6
− 4
− 2
0
Exercise
1B
1
a Domain = R
Range = [−2, ∞)
b Domain = (−∞, 2]
Range = R

Cambridge Senior Maths AC/VCE Mathematical Methods 3&4

ISBN 978-1-107-56747-4

Photocopying is restricted under law and this material must not be transferred to another party.

© Evans et al. 2016

Cambridge University Press

Answers

1B

Answers

775

Domain = (2, 3)

Range = [0, 9)

Domain = (3, 1)

Range = (6, 2)

Domain = [4, 0]

Range = [0, 4]

Domain = R

Range = (−∞, 2)

c

d

e

f

2 a

y 1 x 0 Domain = R Range = [1, ∞)
y
1
x
0
Domain = R
Range = [1, ∞)
c y 2 x 0 8 Domain = [0, ∞)
c
y
2
x
0
8
Domain = [0, ∞)

Range = (−∞, 2]

e

y 5 x 0 5 Domain = [0, 5]
y
5
x
0 5
Domain = [0, 5]

Range = [0, 5]

g y (2, 4) 0 x − 1 −2 2 − 5 ( − 1,
g
y
(2, 4)
0
x
− 1
−2
2
− 5
(
− 1, − 5)
Domain = [−1, 2]
Range = [−5, 4]

b

y

 
3 − 3 0 3 − 3
3
3
0
3
3

x

Domain = [3, 3]

Range = [3, 3]

d

y

(1, 2) 0
(1, 2)
0

(4, 4)

 

x

 

Domain = [0, ) Range = [0, )

f

y

(4, 18)

2 0 4
2
0
4

x

Domain = [0, 4] Range = [2, 18]

h

y

4 − 2 2 x 0 Domain = R Range = (−∞, 4]
4
− 2
2
x
0
Domain = R
Range = (−∞, 4]
i y Domain = R Range = R 1 x 0 1
i
y
Domain = R
Range = R
1
x
0
1

3

4

a Not a function; Domain = {−1, 1, 2, 3}; Range = {1, 2, 3, 4}

b A function; Domain = {−2, 1, 0, 1, 2}; Range = {−4, 1, 0, 3, 5}

c Not a function; Domain = {−2, 1, 2, 4}; Range = {−2, 1, 2, 4, 6}

d A function; Domain = {−1, 0, 1, 2, 3}; Range = {4}

a A function; Domain = R; Range = {4}

b Not a function; Domain = {2}; Range = Z

c A function; Domain = R; Range = R

d Not a function; Domain = R; Range = R

e Not a function; Domain = [4, 4]; Range = [4, 4]

5

a

f (1) = 2,

f (2) = 16,

f (3) = 6,

f (2a) = 8a 2 + 8a

b

g(1) = 10,

g(2) = 14,

g(3) = 54,

g(a 1) = 2a 3 6a 2 + 8a 10

6 a g(2) = 10,

g(4) = 46

b

i

12x 2 2

ii

3x 2 12x + 10

iii

3x 2 + 12x + 10

iv

3x 4 2

3

7 a 3

b 7

b

x > 3

c

2

x =

+ 4

2

c

d

(3, )

8 a x = 3

9 a

3

f : R R, f(x) = 2x + 3

f : R R, f(x) = 3 4 x

f : [0, ) R, f (x) = 2x 3

f : R R, f(x) = x 2 9

f : [0, 2] R, f (x) = 5x 3

10

b

c

d

e

a

c

y

(6, 7) (2, 3) x 0 Range = [3, ∞) y 1 1 − 2
(6, 7)
(2, 3)
x
0
Range = [3, ∞)
y
1
1
2
x
0

b

y x 0 (2, −1)
y
x
0
(2, −1)

Range = (−∞, 1]

d

y (3, 11) 2 − 3 2 x 0
y
(3, 11)
2
3
2
x
0

(

4, 7)

Range = (−∞, 11)

Range = [7, )

e

y f (3, 4) − 1 1 x 0
y f
(3, 4)
− 1
1
x
0

Range = (−∞, 4]

g y h ( −5, 14) ( −1, 2) x 0 Range = [2, 14]
g
y
h
(
−5, 14)
(
−1, 2)
x
0
Range = [2, 14]
y (6, 17) 1 3 x − 1 0 ( − 2, − 7) Range
y
(6, 17)
1
3
x
1
0
(
− 2, − 7)
Range = [−7, 17]
y (4, 19) 0 x −1 0.2 ( −2, − 11) Range = (−11, 19)
y
(4, 19)
0
x
−1
0.2
(
−2, − 11)
Range = (−11, 19)

11 a f (2) = 3,

b g(2) = 7,

c

f (3) = 37,

g(1) = 1,

f (2) = 21

g(3) = 9

i

f(a) = 2a 2 6a + 1

ii

f (a + 2) = 2a 2 + 2a 3

iii

g(a)

= 3 + 2a

iv g(2a) = 3 4a

v

f (5 a) = 21 14a + 2a 2

vi

f (2a) = 8a 2 12a + 1

 

vii

g(a) + f (a)

=

2a 2 8a + 4

viii

g(a) f (a) = 2 + 4a 2a 2

viii g ( a ) − f ( a ) = 2 + 4 a −

Cambridge Senior Maths AC/VCE Mathematical Methods 3&4

ISBN 978-1-107-56747-4

Photocopying is restricted under law and this material must not be transferred to another party.

© Evans et al. 2016

Cambridge University Press

1C

Answers

776

Answers 12 a 2 ,−1 b − 2 , 2 c 0, − 1 3
Answers
12
a
2 ,−1
b − 2 , 2
c 0, − 1 3
3
3
3
d
(−∞, −1) ∪ 2 ,∞
3
∪ 2
1
e
−∞, − 2
,∞
f − 3 ,0
3
3
13
a
f (−2) = 2
b
f (2) = 6
c
f(−a) = a 2 − a
d f(a) + f(−a) = 2a 2
e
f(a) − f(−a) = 2a
f
f(a 2 ) = a 4 + a 2
a + 2
14
a
{2}
b
{ x : x > 2 }
c
3
− 8
13
d
e
{1}
f
3
18
4
15
a
b 6
c
− 7
d 9
f − 2
3
3
e 1 3
9
6
1
16
a
b
c
1 d 1
e −1, 2
5
5
± 3
Exercise
1C
1
One-to-one functions: b, c

2

3

4

5

6

7

8

9

One-to-one functions: b, d, f

a

b

y

y

a

Functions: i, iii, iv, vi, vii, viii

One-to-one functions: iii, vii

= √ x + 2, x ≥ −2; Range = R + ∪ {0} =
=
√ x + 2,
x ≥ −2;
Range = R + ∪ {0}
= − √ x + 2,
x ≥ −2;
Range = R − ∪ {0}
y b
g 1 (x) = x 2 + 2,
x ≥ 0
g 2 (x) = x 2 + 2,
x < 0
2
x
0
Domain = R
Range = R
Domain = [0, ∞)
Range = [0, ∞)
Domain = R
Range = [−2, ∞)
Domain = [−4, 4]
Range = [0, 4]
Domain
=
R \ {0}
Range
=
R \ {0}
Domain = R
Range = (−∞, 4]
Domain = [3, ∞)
Range = [0, ∞)
Domain = R
Range = R
Domain = R
Range = [−2, ∞)
Domain = [−3, 3]
Range = [0, 3]
Domain = R \ {1}
Range = R \ {0}
R \ {3}
b
(−∞, − √ 3] ∪ [ √ 3, ∞)
R
d
[4, 11]
e
R \ {−1}
(−∞, −1] ∪ [2, ∞)
g R \ {−1, 2}
(−∞, −2)
[1, ∞)
i 0,
1
3
[−5, 5]
k [3, 12]
y b Range = [−2, ∞)
x
− 1
0 1
2
− 1
− 2

a

b

c

d

e

f

g

a

b

c

d

a

c

f

h

j

a

10

11

12

Domain = (3, 0] [1, 3); Range = [2, 3)

Domain = [−5, 4]; Range = [−4, 0) ∪ [2, 5] a y (2, 10)
Domain = [−5, 4]; Range = [−4, 0) ∪ [2, 5]
a
y
(2, 10)
( − 4, 9)
6
5
x
0
− 4
2
−4

b

a

a

d

e

f

Domain = (−∞, 2]; Range = [5, 10] ∪ {−4}

y b Range = [5, )

( − 3, 8) 8 5 x 0 −3 f (−4) = −8 b f
( − 3, 8)
8
5
x
0
−3
f (−4) = −8
b
f (0) = 0

c

f (4) = 1

4

1

 

 

a + 3 ,

2(a + 3),

1 a > 3

 

2a ,

 

4a,

 

a

2

3

2

f (a + 3) =

 

f (2a) =

a > 0

a 0

f (a 3) =

  

 

1

a 3 ,

2(a 3),

a > 6

6

a

f (8) = 7

c Neither

f Neither

c Odd

f Even

i Even

13

14

15 a f (0) = 4 b f (3) = √ 2 c  
15
a
f (0) = 4
b
f (3) = √ 2
c
 
√ a,
a ≥ 0
d
f (a + 1) =
 
4,
a < 0
 
√ a − 2,
a
≥ 2
e
f (a − 1) =
 
4,
a < 2
16
y
x
− 2 −1
0 1
−1
− 2
 
 −x − 4,
x < −2
 
1
17
y =
− 1,
−2 ≤ x ≤ 3
 2 x
 
1
− 2 x + 2,
x > 3
18
a
Even
b Odd
d
Even
e Odd
19
a
Even
b Even
d
Odd
e Neither
g
Neither
h Neither
© Evans et al. 2016
Odd e Neither g Neither h Neither © Evans et al. 2016 Cambridge Senior Maths AC/VCE

Cambridge Senior Maths AC/VCE Mathematical Methods 3&4

ISBN 978-1-107-56747-4

Photocopying is restricted under law and this material must not be transferred to another party.

Cambridge University Press

Answers 777 7 y 1 y = (1, 2) x (1, 1) 1 1 y
Answers
777
7
y
1
y =
(1, 2)
x
(1, 1)
1
1
y = +
(
−1, 1)
x
2
x
1
y =
2
x
x
−1
0
local min. at
1
(− 1, − 1)
2, −
4
8 a
y
Answers
1D
(−2, 4) y =√x + 2 (0, √2) (0, 0) x (−2, 0) y =√x
(−2, 4)
y =√x + 2
(0, √2)
(0, 0)
x
(−2, 0)
y =√x + 2 −2 x
y =−2 x

b

y

(0, 2√2) y = √2 − x y = √x + 2 (2, 2) (−2,
(0, 2√2)
y = √2 − x
y = √x + 2
(2, 2)
(−2, 2)
√2
x
−2
0
2

9

y 16 12 8 4 0 2 4
y
16
12
8
4
0
2
4

x

10

y 16 12 8 4 x 0 2 4 − 4
y
16
12
8
4
x
0
2
4
− 4
11 y y = x 2 + 3x + 2 2 y = x 2
11
y
y = x 2 + 3x + 2
2
y = x 2
y = ( f + g)(x)
x
0
y = 3x + 2
2
− 3
© Evans et al. 2016

Cambridge University Press

1D2 2 − 3 © Evans et al. 2016 Cambridge University Press 1 a ( f

1

a

( f + g)(x) = 4x + 2

b

( f + g)(x) = 1

(

f g)(x) = 3x 2 + 6x

( f g)(x) = x 2 x 4

dom = R

 

dom = (0, 2]

c

( f + g)(x) = x + 1

x

 

(

f g)(x) = 1

dom = [1, )

d ( f + g)(x) = x 2 + 4 x

(

f g)(x) = x 2 4 x

dom = [0, 4]

2 a i Even

ii Odd

iii Even

iv Odd

3

1

b ( f + h)(x) = x 2 + 1 + x 2 , even;

1

(gk)(x) = 1, even; ( f h)(x) = 1 + x 2 , even;

( f + g)(x) = x 2 + x + 1, neither;

(g + k)(x) = x + 1 x , odd;

( f g)(x) = x 3 + x, odd

y 6 4 2 0 − 2 2
y
6
4
2
0
− 2
2

x

4

y 12 8 4 0 2 4 6
y
12
8
4
0
2
4
6

x

5

6

y y = x +√x + 2 (2, 4) y = x (2, 2) (0,√2)
y
y = x +√x + 2
(2, 4)
y =
x
(2, 2)
(0,√2)
y =√x + 2
x
0
(−2, −2)
y y = x (1, 1) y = x − x 0 x (1, 0)
y
y = x
(1, 1)
y = x −
x
0
x
(1, 0)
y =− x
(1, −1)

Cambridge Senior Maths AC/VCE Mathematical Methods 3&4

ISBN 978-1-107-56747-4

Photocopying is restricted under law and this material must not be transferred to another party.

Answers 1E 1F

778

Answers 12 a y y = ( f + g)(x) (2, 6) (2, 3) y
Answers
12 a
y
y = ( f + g)(x)
(2, 6)
(2, 3)
y = f(x)
x
(0, 0)
y = g(x)

13

b

a

b

y y = f(x) (1, 1) (− 1, 1) (1, 0) (− 1, 0) −1)
y
y = f(x)
(1, 1)
(− 1, 1)
(1, 0)
(− 1, 0)
−1) (1, − 1)
( −1,
y = ( f + g)(x)
y = g(x)

x

y y = x 2 + 3 ( − 3, 6) y = x 2
y
y = x 2 + 3
(
− 3, 6)
y = x 2
(
y = 3
3, 6)
(
− 3, 3)
(
3, 3)
x
0

y

y = x 2 + 2x + y = x 2 + 2x x y
y = x 2 + 2x +
y = x 2 + 2x
x
y =
x
x
0

c

y

y = x (1, 1) (1, 0) x 0 (1, − 1) y = −x
y =
x
(1, 1)
(1, 0)
x
0
(1,
1)
y = −x 2 +
x
y = − x 2
1E
1 a
f (g(x)) = 4x − 1,
g( f (x)) = 4x − 2
b
f (g(x)) = 8x + 5,
g( f (x)) = 8x + 3
c
f (g(x)) = 4x − 7,
g( f (x)) = 4x − 5
d
f (g(x)) = 2x 2 − 1,
g( f (x)) = (2x − 1) 2
− 5 d f (g(x)) = 2x 2 − 1, g( f (x)) = (2x −

e

f

2 a

f (g(x)) = 2(x 5) 2 + 1,

f (g(x)) = 2x 2 + 1, f (h(x)) = 6x + 3

15

g( f (x)) = 2x 2 4

g( f (x)) = (2x + 1) 2 b h( f (x)) = 6x 1

g 3

c

a 9x 2 + 12x + 3

c 120

d 11

e 21

f 7

3

b 3x 2 + 6x + 1

e 3

d 46

f 1

4 a h(g(x)) =

1

(3x + 2) 2 ,

dom(h g) = R +

5

6

7

3 2 + 2,

x

d 5

b

g(h(x)) =

1

25

dom(g h) = R \ {0}

ran g = [0, )

ran( f g) = [4, )

=

R

x 0

1

ran

=

R \ {

1

2 }

ran = R \ {0}

y 0 1 2 − 1 − 2
y
0 1
2
− 1
− 2

x

c

a

b

c ran f dom g

a

b

a ran f = [2, ) dom g = R + ∪ {0}

b

ran f = [4, ),

f g(x) = x 4,

f g(x)

g f (x) = x,

x,

=

dom

dom = R \ {0],

\ { 2 },

f g(x) = x 2,

8

9

a ran g = [1, ) dom f = (−∞, 3]

b g : [2, 2] R,

g (x) = x 2 1

f g : [2, 2] R,

f g (x) = 4 x 2

a ran g = R dom f = R +

b g 1 : (−∞, 3) R,

g 1 (x) = 3 x

10

Domain

Range

f

g

R

[0, )

(−∞, 3]

[0, )

11

a ran g dom f , so f g exists

b ran f dom g, so g f does not exist

a S

b

c ran f dom g, so g f is defined ran g dom f , so f g is not defined

= [2, 2]

ran f = [0, 2], ran g = [1, )

12 a ∈ [2, 3] Exercise 1F
12
a ∈ [2, 3]
Exercise
1F

1 a

f 1 (x) = x 3

2

b

f

1 (x)

= 4 x

3

c

f 1 (x) = x 3

4

2 f 1 (x) =

a

x + 4

c

f 1 (x) = 4x

3

3 a

f 1 (x) =

1

2 (x + 4)

dom = [8, 8]

ran = [2, 6]

c

h

1 (x) = x 2

dom = [2, )

ran = R + ∪ {0}

b f 1 (x)

d

f 1 (x)

=

=

x

2

4x + 2

3

b

d

g 1 (x) = 9 1

x

dom = (−∞, 0)

ran = (9, )

f 1 (x) =

1

5 (x + 2)

dom = [17, 28]

ran = [3, 6]

e

g

1 (x) = x + 1

dom = (0, )

ran = (1, )

f

h 1 (x)

= x 2

dom = (0, )

ran = (0, )

Cambridge Senior Maths AC/VCE Mathematical Methods 3&4

ISBN 978-1-107-56747-4

Photocopying is restricted under law and this material must not be transferred to another party.

© Evans et al. 2016

Cambridge University Press

1F

4 g −1 (x) = √ x + 1 − 1 dom g −1 =
4 g −1 (x) = √ x + 1 − 1
dom g −1 = [−1, ∞), ran g −1 = [−1, ∞)
a
b
y
1
x
− 1
0 123
− 1
1 5 f −1 : R \ {−3} → R, f −1 (x) = x
1
5 f −1 : R \ {−3} → R, f −1 (x) =
x + 3
y
f − 1
x
3
0
3
f
, −3 + √ 13
Intersection points: −3 + √ 13
2
2
−3 − √ 13 , −3 − √ 13
2
2

6 f 1 (2) =

2 1 , dom f 1

= [3, 3]

7 f 1 (x) = x

a

2 , dom f 1 = [2, 6], ran f 1 = [1, 3]

b

c

d

e

f

g

f 1 (x) = x + 2 4

dom f 1 = [4, ), ran f 1 = [0, )

{(6, 1), (4, 2), (8, 3), (11, 5)}, dom = {6, 4, 8, 11}, ran = {1, 2, 3, 5}

h 1 (x) = x 2 , dom h 1 = R + , ran h 1 = R

,

f 1 (x) = x

g 1 (x) = 1 + x, dom g 1 = (0, 16), ran g 1 = (1, 3)

g 1 (x) = x 2 + 1, dom g 1 = R + ∪ {0}, ran g 1 = [1, )

3

1, dom f 1 = R, ran f 1 = R

h h −1 (x) = √ 4 − x 2 , dom h −1 =
h
h −1 (x) = √ 4 − x 2 ,
dom h −1 = [0, 2], ran h −1 = [0, 2]
8 y = x − 4
a
y
2
dom = R
y = 2 x + 4
( x − 4)
ran = R
y =
2
(0, 4)
(
− 2, 0)
x
0
(4, 0)
(0, −2)

b

c

d

e

Answers 779 f −1 (x) = 3 − 2x y dom = R 3 ran
Answers
779
f
−1 (x) = 3 − 2x
y
dom = R
3
ran = R
3
2
x
0
3
3
2
3 − x
y = 2
y = 3 − 2 x
Answers
f −1 (x) = √ x + 2 y = (x − 2) 2 y
f −1 (x) = √ x + 2
y = (x − 2) 2
y y = 2 +
x
dom = R + ∪ {0}
ran = [2, ∞)
(0, 2)
x
0
(2, 0)
f −1 (x) = √ x + 1
y
dom = R + ∪ {0}
y =
x + 1
ran = [1, ∞)
y = (x − 1) 2
(0, 1)
x
0 (1, 0)
f −1 (x) = 2 − √ x
y
dom = R + ∪ {0}
y = (x − 1) 2
ran = (−∞, 2]
(0, 4)
(0, 2)
(4, 0)
x
0
(2, 0)
y =− x + 2
f f −1 (x) = 1 x y dom = R + 1 ran =
f
f
−1 (x) = 1
x y
dom = R +
1
ran = R +
y = x
x
0
1
g
f −1 (x) =
y
√ x
dom = R +
1
y = x 2
ran = R +
1
y =
x
x
0
h
h −1 (x) = 2x + 4
y
dom = R
y
= 2x + 4
ran = R
4
1
y
=
(x − 4)
2
x
− 2
0
4
−2

Cambridge Senior Maths AC/VCE Mathematical Methods 3&4

ISBN 978-1-107-56747-4

Photocopying is restricted under law and this material must not be transferred to another party.

© Evans et al. 2016

Cambridge University Press

1F

Answers

780

Answers

9

a f 1 : [2, ) R,

f 1 (x) = (x 2) 2

b f 1 : R \ {0} → R,

c

f

1 (x) =

1

x

+ 3

f 1 : [4, ) R,

f 1 (x) = (x 4) 2 + 2

d f 1 : R \ {1} → R,

f 1 (x) =

x

3 1 + 2

e f 1 : R \ {−1} → R,

f

1 (x) =

5

x + 1 + 1

f f 1 : [1, ) R,

f 1 (x)

= 2 (x 1) 2

10 a f −1 : R \ {1} → R, b f −1 : R
10
a
f −1 : R \ {1} → R,
b f −1 : R + ∪ {0} → R,
c f −1
: R \ { 2 } → R
3
11
a
y b
(3, 3)
x
0 (0, 0)
c
y d
3
2
x
0
2 3

y

 

e y

 
f y (1, 1) x (0, 0) (− 1, −1) h y x 0 y
f
y
(1, 1)
x
(0, 0)
(− 1, −1)
h
y
x
0
y = −2
c D
d A
0 2 y y = 3 0 − 1 , 0 3
0
2
y
y = 3
0
1 , 0
3
 
3 3 −3 0 − 3 g y 0 a C b B
3
3
−3 0
− 3
g y
0
a C
b B

x

x

x

x

y

12

(4, 2) 0 y − 1 2 , 0 y = 2 0 (0, −
(4, 2)
0
y
− 1 2 , 0
y = 2
0
(0, − 1)
x
= 1
y x = –1 (0, 6) y = 1 0 ( − 6, 0)
y
x = –1
(0, 6)
y = 1
0
( − 6, 0)

y

 

13

a A = (−∞, 3]

 

b b = 0,

g 1 (x) = 1 x,

x [3, 1]

x

14

b = 2,

g 1 (x) = 2 + x + 4

15

a = 3,

f 1 (x) = 3 x + 9

16

a y = 3 x

domain = R \ {0}

b y = (x + 4) 3 2

domain = R

c y = (2 x) 2

 

domain = (−∞, 2]

 

3

x

 

d y =

domain = R \ {1}

x 1

 


e

3

y =

2

5 x + 6

domain = R \ {5}

f 1

y =

4

+ 1

domain = (2, )

(x 2)

3

x

17 a Inverse is a

 

y

 

function

 
3 2 1 0 −3 − 2 − 1 123 − 1 − 2 −
3
2
1
0
−3 − 2 − 1
123
− 1
− 2
− 3
 
(1, 2) 1 + √2 0 x + 1 f −1 (x) = x −
(1, 2)
1 + √2
0
x + 1
f −1 (x)
=
x − 1
f −1 (x) = x 2 + 2
2x + 3
f −1 (x) =
3x − 2
y
(3, 4)
(1, 2)
(4, 3)
(0, 1)
(2, 1)
x
0 (1, 0)

x

 

b Inverse is not

 

a function

 
y 4 3 2 1 0 − 3 − 2 −1 1234 − 1 −
y
4
3
2
1
0
− 3 − 2 −1
1234
1
− 2
− 3

c Inverse is not

 

y

a function

 
4 3 2 1 −3 −2 −1 −1 0 1234 − 2 − 3
4
3
2
1
−3 −2 −1 −1
0
1234
− 2
− 3
y 1 −4 0 1 − 4
y
1
−4 0
1
− 4

x

 

x

x

x

Cambridge Senior Maths AC/VCE Mathematical Methods 3&4

ISBN 978-1-107-56747-4

Photocopying is restricted under law and this material must not be transferred to another party.

© Evans et al. 2016

Cambridge University Press

Answers 1G 1H

18

d Inverse is a function

y

6 5 4 3 2 1 0 123456
6
5
4
3
2
1
0
123456

x

e Inverse is not a function

1

a dom f = R \ { 2 },

y 4 3 2 1 − 4 − 3− 2 − 1 0 1 2
y
4
3
2
1
− 4 − 3− 2 − 1
0 1 2 34
− 1
− 2
− 3
− 4
1
ran f = R \ { 2 },

b

f is defined as ran f dom f

f

f f(x) = x,

x R \ {

1

2 }

y

x

xdom f f f ◦ f ( x ) = x , x ∈ R \

x + 3 1 c f −1 : R \ { 2 } → R,
x + 3
1
c
f −1 : R \ { 2 } → R, f −1 (x) =
2x − 1
Exercise
1G
1 a Maximal domain = R \ {0}; Range = R +
1
1
b
i
ii
iii 16
iv 16
16
16
c
y
x
0
2 a Odd
b Even
c Odd
d
Odd
e Even
f Odd
3 a
x = 1 or x = −1
b
y
g 2 f 0 2 4
g
2
f
0
2
4

x

Answers 4 a x = 1 or x = 0 b y g 1 x
Answers
4 a
x = 1 or x = 0
b
y
g
1
x
0
− 2
2
f −1
1
5 −1 : R → R, f −1 (x) = x
a
f
7
1
b
f
−1 : [0, ∞) → R, f −1 (x) = −x
6
1 1
c
f
−1 : R → R, f −1 (x) =
3
3 x
1 1
d
f
−1 : (16, ∞) → R, f −1 (x) =
4
2 x

781

1H     4 if 0 ≤ x ≤ 2 1 f(x) =
1H
 
4 if 0 ≤ x ≤ 2
1
f(x) =
 
2x
if x > 2
y
8
4
x
0
2
4

2

V(x) = 4x(10 x)(18 x), domain = [0, 10]

3 a A(x) = −x 2 + 92x − 720 b 12 ≤ x ≤
3
a
A(x) = −x 2 + 92x − 720
b 12 ≤ x ≤ 60
c
A
(46, 1396)
(60, 1200)
(12, 240)
x
0

d

Maximum area 1396 m 2 occurs when

x = 46 and y = 34

4 a i S = 2x 2 + 6xh

ii S = 2x 2 +

3V

5

x

b

c

Area = x 4a 2 x 2 , domain = [0, 2a]

Maximal domain = (0, )

Maximum value of S = 1508 m 2

6a 6 a A = a + 2 b Domain = [0, 6]; Range =
6a
6
a
A =
a + 2
b
Domain = [0, 6]; Range = 0, 9
2
9
c
d
y
2
4
9
6,
2
2
0
2
4
6

x

= 0, 9 2 9 c d y 2 4 9 6, 2 2 0 2

Cambridge Senior Maths AC/VCE Mathematical Methods 3&4

ISBN 978-1-107-56747-4

Photocopying is restricted under law and this material must not be transferred to another party.

© Evans et al. 2016

Cambridge University Press

Answers 1 review

782 Answers 1 1 3 7 a a = b = c = 45, d
782
Answers
1
1
3
7 a
a =
b =
c = 45,
d = − 2 ,
e = 75
30 ,
15 ,
b
S
c Range = 0, 7
2
7
75,
2
3
45,
2
t
0
Chapter 1 review

Technology-free questions

1 a Domain = R y Range = [1, ∞) f ( x) = x
1
a Domain = R
y
Range = [1, ∞)
f ( x) = x 2 + 1
(0, 1)
x
0
b Domain = R
y
Range = R
f(x) = 2x − 6
x
0
3
− 6
c Domain = [−5, 5] y Range = [−5, 5] 5 x 2 + y
c Domain = [−5, 5]
y
Range = [−5, 5]
5
x 2 + y 2 = 25
x
− 5
0
5
− 5
d Domain = R
y
5 x 2 + y 2 = 25 x − 5 0 5 − 5 d

Range = R

e Domain = R

Range = R

y ≥ 2x + 1 1 0 1 − 2 y y < x −
y ≥ 2x + 1
1
0
1
2
y
y < x − 3
3
0
− 3

x

x

2

3

4

5

6

7

8

9

a y (5, 4) 3 y = g ( x ) 2 x 0 −3
a
y
(5, 4)
3
y = g ( x )
2
x
0
−3
b
ran g = 3 2 ,4
3
c
g −1 : 2 ,4 → R, g −1 (x) = 2x − 3
dom g −1 = 3 2 ,4 ,
ran g −1 = [0, 5]
7
d
{5}
e
2
5
1
a
b
{11}
c −
1
10
y
(2, 3)
x
0
1
2
(0, −1)
a
R \ {3}
b
R \ [− √ 5, √ 5]
c R \ {1, −2}
d
[−5, 5]
e
[5, 15]
f R \ {2}
(
f + g)(x) =
x 2 + 5x + 1,
(
f g)(x) = (x − 3)(x + 2) 2
(
f
+ g): [1, 5] → R, ( f
+ g)(x) = x 2 + 1
(
f g): [1, 5] → R, ( f g)(x) = 2x(x − 1) 2
f −1 : [8, ∞) → R, f −1 (x) = √ x + 1

a ( f + g)(x) = x 2 + 2x + 3

b ( f g)(x) = x 2 (2x + 3)

c {−1, 3}

10 y y = x 0, 4 (2, 2) 3 x ( −4, 0) 0
10
y
y = x
0, 4
(2, 2)
3
x
(
−4, 0)
0
4 , 0
3
(0, −4)
1 1
11
a
f −1 : R → R, f −1 (x) =
3
2 x
1 1
b f −1 : (−∞, 0] → R, f −1 (x) =
5
2 x
1 1
c f −1 : [0, ∞) → R, f −1 (x) =
6
2 x

d f 1 : (10 000, ) R, f 1 (x) =

1 1

10 x

4

12 a f g(x) = 2x 3 + 3

b g f (x) = (2x + 3) 3

c g g(x)